PROSES PEMBUATAN KAIN SONGKET TENUN DI DESA UJUNG TANAH KECAMATAN SAMADUA KABUPATEN ACEH SELATAN - Susana, Susana; Ismawan, Ismawan; Nurlaili, Nurlaili (Jurnal Ilmiah Mahasiswa Sendratasik, 2018)
ABSTRACTThe research, entitled "The Process of Making Woven Songket Ujung Tanah Village, Samadua, South Aceh" raised the problem how the process of making woven songket in Ujung Tanah Village, Samadua, South Aceh. This research aims to describe the process of making woven songket in Ujung Tanah Village, Samadua, South Aceh. The approach in this research is a qualitative approach and type of research used is qualitative research with descriptive methods. The source of the data in this research is Anita Suryani and Hasfamaidar who are songket weaving craftsmen in Ujung Tanah Village. The object in this study is the process of making songket in Ujung Tanah Village, Samadua, South Aceh. Data collection techniques are used with observation, interview and documentation techniques. Data analysis techniques use an inductive approach which includes 3 steps, namely: Data reduction, Data presentation and Data verification. The results of data analysis showed that the process of making songket fabric consisted of 5 stages, namely: Meuhani, Menyusuk, Menyisir, Making Motifs and Weaving.Keywords: process, making, songket weaving.